Studi Manajemen Parkir di Kawasan Pasar Kuok Kabupaten Kampar Provinsi Riau - Anugrah, Ihsanul Arkan; Ningrum, Puspa; Toyeb, Muhammad (Journal of Infrastructure and Civil Engineering, 2022)
One of the regencies in the province of Riau is Kampar. Pasar Kuok is one of the well-known markets in Kampar Regency, a Regency that continues to employ traditional markets as shopping destinations for the neighborhood. Traffic congestion is a common occurrence in Pasar Kuok, especially on market days like Tuesdays. Therefore, a research on parking management is required to ensure that the demand for parking spots can be met. In order to solve issues that exist in the Pasar Kuok area, this study intends to determine the availability of existing parking lots, identify the effects of parking activities, and and obtain scenarios as an alternative to solving problems. Data from the (a) Parking Patrol, (b) parking volume, and (c) parking inventory must all be collected. Based on the survey, there are two types of parking available at Pasar Kuok: on-street parking (using the road) and off-street parking (not using the road). After analyzing the data regarding the existing parking conditions as well as the problem solving recommendations, the results obtained from the analysis that have been carried out, given three scenarios for parking repairs, in order to be an alternative to solve existing problems. The first alternative is to change the width of the parking space unit capacity (SRP) for motorcycles. The second alternative is to change the location of the parking lot on the car street into a motorbike parking lot. The third alternative is to move the motorbike parking lot on Jalan Pulau Balai to the on-street motorcycle parking area located on Jalan Lintas Pekanbaru – West Sumatra A.